Economic and Accounting Interpretative Approach on Income Disparity: Evidence from China - Wong, E.S.K. (Canadian Center of Science and Education (CCSE), 2010)
In this paper, we analyse the current China urban and rural income disparity. Our analysis demonstrates that the Economic and Policy reforms instituted by the Chinese government over the past decade or so have had two primary aims: Firstly, to maintain political stability at all costs and secondly to transform China into a modern industrial state. To ensure political stability, it has eschewed the current Russian model for a unique Chinese model where state owned enterprises co-exist with market driven businesses. This all began in 1978, after two disastrous near revolutions where the hard-line Marxist-Socialists had to concede that all was not well for the future of China, in a modern world. Beginning with the rural sector, where the pool of greatest poverty existed and improving in that sector firstly, allowed the market-oriented to greatly improve their incomes, thus changing the disparities between urban and rural economics. The period of 1985 to 2005 was a period of almost exponential growth, and the raising of millions out of poverty was only part of the positive results, but the greatest social negative was that inequality became worse, as is found in most Capitalist societies. There seems to be an initial jump in the incomes of rural China to jump out of poverty, but the effects have slowed, and it is now up to government agencies to aid the remaining impoverished to escape the traps of poverty through education and relocation incentives for industry, domestic and foreign. This does not mean throwing money at the problem, it means preventing destitution, as destitution adds to crime and other anti-social events and greatly increases instability, the anti-thesis of current Chinese policy. Perhaps the question ought to be a rethink of agricultural policies, to generate corporate farming, as opposed to collective farming, all in order to reduce rural poverty and make rural businesses into a proper and profitable sector of employment.